Revision of the genus Stenichnaphes Franz in New Zealand (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
Three species of Stenichnaphes Franz were described from New Zealand: St. urbanus Franz (type species of the genus), St. peloriensis Franz and St. newtoni Franz, but the two former names were later synonymized. Basing on detailed morphological study, St. peloriensis is reinstated as a separate species, and St. newtoni is transferred to Scydmaenilla King, within Zeanilla subg. n., resulting in Scydmaenilla (Zeanilla) newtoni comb. n. All three species are redescribed, a previously unknown aedeagus of St. peloriensis is illustrated, and details of morphological structures of St. urbanus and Sc. newtoni are presented.